Clinicians' Beliefs and Practices Regarding Drug Use Care of Their Community Health Center Patients. Issue 6 (November 2015) - Reddy, Anjani T.; Andersen, Ronald M.; Gelberg, Lillian
Abstract : Objectives: Integration of behavioral health including substance use problems into primary care is an essential benefit that federally qualified health centers (FQHCs) will offer as part of the Affordable Care Act. This study explores FQHC primary care clinicians' beliefs and practices regarding illicit drug use assessment and treatment. Methods: We administered a 10-minute questionnaire to 68 primary care clinicians of 5 FQHCs in Los Angeles. Results: Clinicians expressed limited confidence in their ability to address patients' illicit drug use, scoring on average 3.31 on a 5-point Likert scale. Two thirds reported that they assess for drug use routinely "at every visit" and/or "at annual visits." When asked how often they counsel regarding drug use (on a 5-point Likert scale from "never" to "always"), the median response was 4 ("usually"). Regarding their perspectives on the best practical resource for addressing drug use in their clinics, 45.6% named primary care clinicians. A minority (29.4%) of clinicians had completed a clinical rotation dealing with substance use, and 27.2% reported receiving more than 10 hours of training regarding substance use problems. Having a substance use rotation was associated with greater confidence in drug use assessment and treatment ( P  < 0.01). More hours of substance use training was associated with greater confidence ( P  = 0.01) and routinely addressing substance use in their patients ( P  = 0.04). Conclusions: Although two thirds of the surveyed clinicians assess for drug use routinely, and on average, report that they usually address drug use, clinicians' confidence in substance use care seems to be suboptimal, but both confidence and routinely addressing substance use are associated with increased substance use education. Improving clinicians' training and integrating drug use care in FQHCs may improve confidence in substance use care and facilitate the Affordable Care Act's mandate to integrate behavioral health into routine FQHC primary care.